US Monetary Policy in a Globalized World - Jesús Crespo-Cuaresma; Gernot Doppelhofer; Martin Feldkircher; Florian Huber (Center for Economic Studies and ifo Institute (CESifo), 2016)
We analyze the interaction between monetary policy in the US and the global economy, using a global vector autoregressive model with time-varying parameters and stochastic volatility (TVP-SV-GVAR). We find that a contractionary US monetary policy shock leads to a persistent fall in international output, a drop in global inflation rates, a rise in international interest rates and a strengthening of the US dollar in real terms, with heterogeneous transmission effects across countries and over time. US short-term rates decrease significantly in response to a monetary policy tightening abroad or a negative shock to foreign real GDP growth.
Keywords: C30; E52; F41; 330; global vector autoregression; time-varying parameters; stochastic volatility; monetary policy; international spillovers